The Effect of Online Communication in a Social Dilemma: - Kaori Ando; Akihito Himuro; Akira Goto; Yuuji Sasaka; Naoya Ejima; Akiko Yasuhara (Maketingu Janaru)
Most environmental problems face social dilemmas. Focusing on the effects of communication, this study examined whether or not online text-based communication affects the cooperation rate in social dilemmas. For this purpose, we developed an online game that simulates environmental problems using a social dilemma structure. In the game, a participant decides how much recyclable waste they dispose of (cooperative behavior) out of the waste generated in a group of three members. The results of the experiment showed that the rate of cooperation was higher after having chatted with other members, indicating the effectiveness of communication. The groups in which all members agreed to cooperate with the entire amount had a higher cooperation rate than the other groups. These results show that online chat communication can promote cooperation in social dilemmas.